A Bibliometric Analysis: Trend of Studies in Self-Regulated Learning Over The Past Three Decades - Sulistiawati Sulistiawati; Yaya Sukjaya Kusumah; Jarnawi Afgani Dahlan; Dadang Juandi; Hans Vos (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
Many studies measure self-regulated learning in some fields but still a few studies in the education field or related fields. This study aimed to analyze performance analysis and science mapping related to the research trend in self-regulated learning over the past three decades. Therefore, it was conducted using the bibliometric analysis method on 2106 documents related to self-regulated learning published in the period 1990-2022 from the Scopus database. Those documents are limited in the final stage, English, journal source type, and article document type. The chosen subject areas were art and humanities, psychology, and social sciences which have a relation with the education field. The data analysis process was assisted by Publish or Perish and VOSviewer software to examine the publication and citation-related metric, publication, and citation trend analysis, citation analysis, co-authorship analysis, and co-word analysis. The results of this study are the trend and development of research regarding self-regulated learning over the past three decades presented that: 1) the publication-and-related metric in this study showed that there were 2,106 papers related to self-regulated learning which distributed in range 1990-2022 that has 20,752 citations and the h-index value is lower than g-index value, 2) the publication-and-citation trend analysis showed relatively fluctuative in periods and constant in particular year, 3) the citation analysis showed that the most influential document is written by B. J. Zimmerman in 2008 that has been cited around 1664 times, 4) the author who has collaborated the most with other authors is Järvelä, S., 5) the United Stated is the most productive and influential country who make studies in self-regulated learning, 6) the most productive organization is University of Oulu, Finland and the the most influential organization is the Department of Educational Psychology, Graduate Center, City University of New York, and 7) the ‘self-regulated learning’ keyword has the most occurrence amount 1766 times. These findings provide an overview of the evolution of self-regulated learning research papers during the last three decades. This study examines a period of time that was longer than previous studies. As a consequence, its resulting contribution is also larger, providing an overview of the field's evolution over the last 30 years and providing other researchers with a comprehensive resource for performing self-regulated learning research.